2021
DOI: 10.3389/fimmu.2021.728669
|View full text |Cite
|
Sign up to set email alerts
|

CD49a Identifies Polyfunctional Memory CD8 T Cell Subsets that Persist in the Lungs After Influenza Infection

Abstract: CD8 T cell memory offers critical antiviral protection, even in the absence of neutralizing antibodies. The paradigm is that CD8 T cell memory within the lung tissue consists of a mix of circulating TEM cells and non-circulating TRM cells. However, based on our analysis, the heterogeneity within the tissue is much higher, identifying TCM, TEM, TRM, and a multitude of populations which do not perfectly fit these classifications. Further interrogation of the populations shows that TRM cells that express CD49a, b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 64 publications
2
25
0
Order By: Relevance
“…All children with active TB were culture negative and symptom free at the end of ATT. The demographic and epidemiological data have been previously reported [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…All children with active TB were culture negative and symptom free at the end of ATT. The demographic and epidemiological data have been previously reported [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…CD8 + T RM cells are defined by co-expression of CD69 and integrin α E sub-unit (CD103) [7]. In addition, in the lungs of humans and mice, T RM cells can also express integrin α 1 sub-unit (CD49a) and CCL16 chemokine receptor CXCR6 [8][9][10] but are heterogeneous and exhibit different expression levels of other surface markers [11,12]. In the lungs, T RM cells are important for the control of viral respiratory infections, as well as being the main drivers of heterosubtypic immunity to influenza A (IAV) infection [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…CD49a and CD69 play well-established roles in TRM cell survival, trafficking, and retention, while the role of CD103 on the lung TRM cells is less understood, although it has been suggested to promote epithelial adherence ( 87 ). In particular, recent work has demonstrated that CD49a is a common marker of TRM cell cytolytic activity irrespective of CD103 expression ( 88 ). In line with these reports, we observed that Blimp-1 hi TRM cells from lung allografts with BOS expressed high levels of CD49a and Grzmb readily killed pulmonary epithelial cells.…”
Section: Discussionmentioning
confidence: 99%